El Varrón gramático en la Minerva de Francisco Sánchez de las Brozas (Minerva, 2019)
In the Minerva, Sanctius uses Varro, the grammarian, several times and in different ways: the even ascribes to him a text which comes from Ramus. Some quotations of the Roman writer are already in earlier works of Sanctius. But this one neither admires Varro clearly nor identifies himself with his theories nor shows a systematic study of these ones: he makes use of Varro as long as this scholar supports his own theory and he manipulates him if it si necessary.Sanctius takes this use of Varro especially from Ramus and Alvares, though he sometimes modifies it. The main sources of his quotations, at least remotely, are the Augustinus’ and the Vertranius’editions of De lingua Latina.